Cost management system practiced by Zakat Collection Centers in Melaka, Negeri Sembilan, Pulau Pinang, Wilayah Persekutuan and Selangor: an exploratory study / Hamidah Bani, Norzehan Abu Bakar and Maheran Katan - Bani, Hamidah; Abu Bakar, Norzehan; Katan, Maheran (2006)
This research attempts to obtain the empirical data on cost management system being adopted by five corporatized Zakat Collection Centers in Malaysia, classification of cost and the relationship between cost and zakat collection. It was found that the five corporatized zakat centers under study use traditional cost management and cost is classified departmentally. Adapting Hurley and Touran (2002), the cost structure incurred by zakat collection centers can be divided into four categories; salary, fixed assets, administration cost and promotion. After using Chi-square test - cramer coefficient it was found that only promotion has a significant contribution towards zakat collection. However, the significant relationship is in perverse direction where the higher the promotional cost, the lesser the impact on zakat collection. Labour, administrative and fixed asset cost has no significant relationship to the zakat collection.